Recent advances in feeder-free NK cell expansion as a future direction of adoptive cell therapy - Lee, Jimin; Kim, Munsik; Jeong, Hanbin; Noh, Ilkoo; Park, Jeehun (Frontiers in Immunology, 2025)
Adoptive cell therapy has progressed rapidly following the success of CAR-T therapy, with NK cells emerging as strong candidates for next-generation treatments. NK cells naturally recognize abnormal cells without genetic modification and do not cause graft-versus-host disease, making them suitable for mass production from donor blood. Traditional NK cell expansion often relies on cancer-derived feeder cells, posing safety and quality concerns. This review examines both feeder cell-based and feeder-free NK cell culture methods. We analyze the limitations of feeder-based approaches and categorize feeder-free strategies, including cytokine combinations, antibody stimulation, blood components, nanoparticles, and hydrogels. Among these, nanoparticle-based methods show strong potential for enabling safe, scalable, and standardized NK cell expansion without the risks associated with feeder cells. In this paper, we review recent advancements in NK cell culture techniques and propose the potential of nanoparticle technology in developing feeder-free NK cell culture methods.